Exploring the Link Between Biofilm Formation and Multidrug Resistance in Escherichia coli Isolated from Urinary Tract Infections in Sialkot, Pakistan - Shehzadi, Kanwal; Adalat, Rooma; Sattar, Hafiz Abdul; Ehsan, Hira; Manzoor, Saba; Nisar, Uzma; Alyas, Sobia; Ilyas, Sadaf (Biological and Clinical Sciences Research Journal, 2025)
Escherichia coli strains are among the key contributors to urinary tract infections (UTIs) around the world, presenting a significant health challenge globally. Objectives: This cross-sectional study aims to isolate multidrug-resistant (MDR) Escherichia coli strains from UTI patients in Sialkot, Pakistan, and to investigate their biofilm-forming ability, exploring the possible association between biofilm formation and antibiotic resistance. Methods: A total of 131 E. coli isolates were isolated and identified. Their ability to form biofilms was confirmed using the tube method, and their antibiotic susceptibility patterns were evaluated using the disc diffusion method. Fisher's exact test was applied to investigate the association between biofilm production and antibiotic resistance. Results: The findings revealed that 65.6% isolates (n = 88) were biofilm producers, while 34.4% (n = 43) were non-biofilm producers. Antibiotic sensitivity testing indicated high levels of resistance among isolates to several antibiotics, notably ceftriaxone (91.6%), cefoperazone (86.3%), ciprofloxacin (85.5%), cefotaxime (82.4%), and cefixime (81.7%). A significant association was observed between biofilm formation and resistance to most antibiotics, including nitrofurantoin, amoxicillin-clavulanate, amikacin, piperacillin-tazobactam, and sulfamethoxazole-trimethoprim, among others. Conclusion: These findings suggest that E. coli isolates resistant to these certain antibiotics are more likely to form biofilms. This research highlights the critical need to explore biofilm formation, along with antibiotic susceptibility patterns of isolates, to help select appropriate antibiotics and facilitate effective treatment approaches.